HUKUM PIDANA KORUPSI DALAM TAFSIR AL-JAMI’ AL-AHKAM AL-QUR’AN KARYA AL-QURTUBI - Iwan Setiawan (LP2M Universitas PTIQ Jakarta, 2025)
This study examines criminal law on corruption from the perspective of Imam Al-Qurthubi’s Quranic exegesis, Al-Jami’ li Ahkam Al-Qur’an. Corruption, as a crime harming state finances and society, is analyzed through relevant Quranic verses such as risywah (bribery), gulul (embezzlement), and gasab (usurpation), alongside Al-Qurthubi’s interpretations. The research employs a thematic (maudu’i) approach and descriptive analysis of literature. Findings reveal that Al-Qurthubi categorizes corruption as a violation of justice and trust, referencing the concept of suht (ill-gotten wealth), which includes bribery and embezzlement. In Islamic criminal law, corruption does not fall under hudud or qishash but ta’zir, where penalties are determined by authorities based on social and moral impacts. Recommended ta’zir punishments include double restitution, exile, lashing, dismissal from office, imprisonment, and capital punishment for severe cases. The study also highlights the relevance of classical exegesis to modern contexts, particularly in combating corruption in Indonesia. It concludes that integrating sharia principles through ta’zir and positive law enforcement is essential to deter corruption and uphold social justice.